Prognostic validity of swim-specific performance prerequistes in elite crawl sprint - Hohmann, A.; Neumann, T.; Frankel, J. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
It was shown that fully-tethered swimming is an objective, reliable and valid tool for measuring swimming force and swimming technique, represented by quantifying the mean force and the intra- and intercyclic variation of the propulsive force exerted by the swimmers in a fully tethered 6-sec-maximum crawl sprint test. The influence of fatigue over the 6 s was partialized out of the force-time curve by regression analysis. From the stationary force-time curve of each individual (i) the mean force, and (ii) the standard deviation of the force variation was calculated, and then expressed as %age of the mean force. A small intra- and intercyclic variation of the swimming force was then interpreted as a high technical proficiency of the swimmer. In the follow-up study with all male (n = 33) and female (n = 27) participants of the European Junior Championships 2007 and 2008 a significant correlation between the width of the arm span, swimming force, and swimming technique at junior age, and the M = 6.85 years (SD = 3.26) later 50-m-crawl sprint performance at adult age was found. Furthermore, a discriminant analysis corroborated the prognostic validity of the swim-specific testing on elite performance Level.